Penerapan Respiration Training Untuk Meningkatkan Durasi Fonasi Pada Pasien Disfonia Neurogenik Dewasa - Agustina; Fierda Pramesthi Cahyani Putri (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2025)
Background: Neurogenic dysphonia is a voice disorder resulting from dysfunction of the nervous system that affect action of vocald cords and controls phonatory mechanisms. One of the key parameters in assessing phonatory ability is maximum phonation time, which reflects the coordination between respiratory and phonatory systems. Respiration training is a training for improving breathing efficiency and stabilizing subglottal pressure during phonation. Objective: This study aims to determine the effect of respiration training on improving phonation duration in an adult patient with neurogenic dysphonia using a Single Subject Design (A–B–A). Methods: This research is a Single Subject Design (A–B–A) involving one adult participant with condition neurogenic dysphonia. Data were collected by measuring the sustained phonation of the vowel /a/ using a digital stopwatch during the baseline (A₁), intervention (B), and withdrawal (A₂) phases. The intervention was conducted during 10 therapy session and consisted of diaphragmatic breathing and respiration–phonation coordination exercises. Data were analyzed visually and descriptively based on mean phonation duration changes across phases. Results: The average phonation duration increased from 1.70 seconds during the baseline phase to 1.81 seconds after intervention, indicating an improvement of approximately 6.5%. Visual analysis revealed a stable and consistent upward trend in phonation duration during the post-intervention phase. Conclusion: Respiration training has a positive effect on improving phonation duration in adults with neurogenic dysphonia. The findings suggest that structured breathing exercises can enhance respiratory–phonatory coordination and voice production efficiency.